Efficiency in Social Versus Private Agricultural Production: The Case of Yugoslavia - Hofler, Richard A.; Payne, James E. (The Review of Economics and Statistics, 1993)
This paper extends the work of Boyd (1987) by examining the question of efficiency in Yugoslavian agricultural production using the stochastic production frontier. We find the private sector produces with higher output efficiency than the social sector. Next, we examine regional efficiency differences. Our findings reinforce earlier analysis of the economic impact of regional development policy pursued in Yugoslavia. Less developed republics appeared unable to utilize efficiently the large volume of investment resources allocated from the more developed republics via the central government.